Medium Karte: Analyse der Wertschöpfungsstrukturen - Vera Kraus (Friedrich-Alexander-Universität Erlangen-Nürnberg, Institut für Buchwissenschaft, Professur für Buchwissenschaft, insb. E-Publishing und Digitale Märkte, 2016)
– This thesis meets the existing scientific need for an in-depth analysis of the current value creation structures of maps as a medium. The demand for maps has grown significantly, particularly in the past 20 years. This can be ascribed to essential social developments, general increasing mobility, digitalisation and globalisation, in addition to crucial techno-logical progress. Until now, the resulting possibilities for innovative value creation have been most widely recognised and explored by technology companies, with Google leading the way. Their interactive map services complement or replace classical cartographic products in many sectors – a trend which challenges the whole traditional value chain of maps. At which points changes take hold of the value chain has yet to be investigated. An in-depth analysis of the whole complex value creation process of maps as a medium, as provided in this work, must precede such an exploration. The paper identifies seven major value-adding steps, the most important processes taking place and the relationships between them. It also names participating actors and depicts their responsibilities as well as their interactions. Moreover, it monitors where basic structures already show initial signs of change. The resulting value chain illustrates the status quo. Though changes already draw on several different points, a substantial reconfiguration of the overall value chain cannot be identified so far. However, the work focuses on the value creation process as a whole and does not consider changes affecting individual actors' internal processes.
urn:nbn:de:bvb:29-opus4-79003
Keywords: 330; Fachverlage; Geoinformation; Karte; Medienwirtschaft; Wertschöpfung